Antibacterial potential of brown algae (Phaeophyceae) extract-based mouthwash against oral pathogenic bacteria: Potensi obat kumur berbasis ekstrak alga coklat (Phaeophycea) dengan efek antibakteri terhadap bakteri mulut - Baharuddin M. Ranggang; Andi Rifka Rahmayanti; Rahmadita Salsa Putri Agus; Aimannahdah; Ashiilah Nurul Aiman; Muhammad Fadhel Sabirin; Annisa Aulya Arriyahiyah; Rezky Putri Reza Ramadhani (Makassar Dental Journal, 2026)
Oral health disorders are often caused by the growth of pathogenic bacteria, particularly Streptococcus mutans, Porphyromonas gingivalis, and Fuso-bacterium nucleatum. One common preventive measure is the use of mouthwash, although long-term use of chemical mouthwashes such as chlorhexidine often causes side effects, including tooth discolouration, mucosal irritation, and sensory disturbances. The use of natural brown algae (Phaeophyceae) extracts is an attractive alternative because they contain bioactive compounds that are antibacterial and antioxidant, such as fucoidan, polyphenols, and phlorotannins. Various studies have shown that extracts from brown algae species can significantly inhibit the growth of bacteria that cause oral diseases. This potential makes brown algae a suitable active ingredient in the formulation of effective and environmentally friendly mouthwashes. It is concluded that the development of brown algae-based mouthwashes supports the utilisation of marine resources as an innovative solution in the field of oral health.